ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESELAMATAN PELAYARAN KAPAL PENANGKAP IKAN DI PELABUHAN TASIKAGUNG REMBANG - Agus Aji Samekto (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2019)
This research is based on the accidents that happen to Indonesian fishing boats which could threaten the shipping industry safeness and causing considerable losses to ship owners. Problems will arise is safeness does not countered. The purpose of this research is to analyse between independent variable and dependent variable. The population sampling are 68 crews ships at Pelabuhan Perikanan pantai Agung, Rembang. The research methodology use is non-probability technique using incidental type sampling. The data collection method is questionnaire. The data analysing technique is multi linear regression which consists of validity test, reliability test, classic assumsion test and hypothesis test. The result shows that there is positive partial influence between fishing boats crews, ships’ seaworthiness, ships’ life-saving equipment and navigational safety aids to the fishing boats safety voyages. So, it could be concludes yaht the four variables have positive and significant influence to the fishing boats safety voyages. In order to ensure the safeness both crews ships and ship owners, they have to be discipline in following the rules. And for the Port Authority of Bojomulyo, Juwana when issuing the Port Clearance and Seaworthiness Certificate should be more cautious, especially when inspecting the ships stability, design and life-saving equipment. As for the Port Authority officers to always updating their competencies and proficiencies to increase the safeness of voyages.Keywords :     Ship life-saving Equipment, Fishing Boats, Voyages safeness.Penelitian ini dilatar belakangi karena seringnya kecelakaan kapal ikan di Indonesia yang menyebabkan keselamatan pelayaran terancam dan menimbulkan kerugian cukup besar bagi pemilik kapal. Dengan melihat permasalahan yang ada, apabila masalah keselamatan pelayaran di laut tidak diperhatikan dengan baik, dikhawatirkan akan terjadi peningkatan jumlah kecelakaan kapal dari tahun ke tahun, tujuan penelitian ini untuk menganalisis pengaruh antara variabel independen terhadap variabel dependen. Dengan populasi awak kapal yang ada di Pelabuhan Perikanan Pantai Tasikagung, Rembang di ambil sampel sebanyak 68 responden. Metode penelitian yang digunakan dengan teknik non-probability sampling jenis insidental sampling, pengumpulan data menggunakan kuisioner, teknik analisis data yang digunakan adalah teknik analisis regresi berganda meliputi uji validitas, uji reliabilitas, uji asumsi klasik, dan pengujian hipotesis. Hasil persamaan regresi linier berganda diperoleh adanya pengaruh yang positif secara parsial antara sumber daya awak kapal ikan, kelaiklautan kapal, alat-alat keselamatan kapal dan peranan sarana bantu navigasi berpengaruh terhadap keselamatan pelayaran kapal ikan.Kata kunci : Alat-alat keselamatan kapal, Sumber daya awak kapal ikan, Kelaiklautan kapal, Sarana Bantu Navigasi Pelayaran (SBNP),  Keselamatan Pelayaran Kapal Ikan.